Biogenesis of Plant Prevacuolar Multivesicular Bodies - Cui, Yong; Shen, Jinbo; Gao, Caiji; Zhuang, Xiaohong; Wang, Junqi; Jiang, Liwen (Molecular plant, 2016)
Plant prevacuolar compartments （PVCs）, or multivesicular bodies （MVBs）, are single membrane-bound organelles that play important roles in mediating protein trafficking to vacuoles in the secretory pathway. PVC/MVB also serves as a late endosome in the endocytic pathway in plants. Since the plant PVC was iden- tified as an MVB more than 10 years ago,-great progress has been made toward the understanding of PVC/ MVB function and biogenesis in plants. In this review, we first summarize previous research into the iden- tification and characterization of plant PVCs/MVBs, and then highlight recent advances on the mechanisms underlying intraluminal vesicle formation and maturation of plant PVCs/MVBs. In addition, we discuss the possible crosstalk that appears to occur between PVCs/MVBs and autophagosomes during autophagy in plants. Finally, we list some open questions and present future perspectives in this field.